2018
DOI: 10.1038/s41467-018-07429-x
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of maternal barriers by paternal miR159 to initiate endosperm nuclear division in Arabidopsis

Abstract: Sperm entry triggers central cell division during seed development, but what factors besides the genome are inherited from sperm, and the mechanism by which paternal factors regulate early division events, are not understood. Here we show that sperm-transmitted miR159 promotes endosperm nuclear division by repressing central cell-transmitted miR159 targets. Disruption of paternal miR159 causes approximately half of the seeds to abort as a result of defective endosperm nuclear divisions. In wild-type plants, MY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Disruption of paternal miR159 caused arrested and/or delayed endosperm nuclear divisions, resulting from the retention of maternal targets, MYB33 and MYB65, after fertilization (Zhao et al, 2018). Ectopic expression of a miR159resistant version of MYB33 in the endosperm significantly inhibited initiation of endosperm nuclear divisions (Zhao et al, 2018). This suggests that a sperm-enriched miRNA initiates an early division event by removing the roadblock comprising maternal factors.…”
Section: Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Disruption of paternal miR159 caused arrested and/or delayed endosperm nuclear divisions, resulting from the retention of maternal targets, MYB33 and MYB65, after fertilization (Zhao et al, 2018). Ectopic expression of a miR159resistant version of MYB33 in the endosperm significantly inhibited initiation of endosperm nuclear divisions (Zhao et al, 2018). This suggests that a sperm-enriched miRNA initiates an early division event by removing the roadblock comprising maternal factors.…”
Section: Reviewmentioning
confidence: 98%
“…Using both genetic and cell biological approaches, Zhao et al . () showed that sperm‐transmitted miR159 promotes endosperm nuclear divisions by repressing central cell‐transmitted miR159 targets. Disruption of paternal miR159 caused arrested and/or delayed endosperm nuclear divisions, resulting from the retention of maternal targets, MYB33 and MYB65 , after fertilization (Zhao et al ., ).…”
Section: Mirna Accumulation In Pollen and Mirna Function During Seed mentioning
confidence: 99%
See 1 more Smart Citation
“…miR159a.2 was unique to root, while miR159c, d, and e were enriched in egg, and miR159f was enriched in seedling shoot and egg. In Arabidopsis, miR159 family members repress MYB transcription factors and are expressed in multiple tissues including sperm, and paternal miR159 regulates nuclear division in endosperm (Allen et al 2010;Zhao et al 2018).…”
Section: Distinct Mirna Expression Patterns In Gametesmentioning
confidence: 99%
“…Plant miRNAs are typically 20-22 nt in length, and function in posttranscriptional gene silencing through mRNA cleavage or translational repression (Rogers and Chen, 2013). In animals and plants, miRNAs play an important role in male germline and embryonic development (Borges et al, 2011;Conine et al, 2018;Zhao et al, 2018). Another large group of sRNAs in plants constitute the 20 to 24 nt siRNAs, which function primarily in transcriptional gene silencing of viral DNA, transgenes, and transposable elements (TEs; Borges and Martienssen, 2015) through the RNA-directed DNA methylation pathway.…”
mentioning
confidence: 99%